1992
DOI: 10.1002/jrs.1250230505
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectra of tetragonal lanthanide oxychlorides obtained from polycrystalline and single‐crystal samples

Abstract: The reported Raman spectra of the tetragonal [lead chlorofluoride-type structure, D~,,-PCl/nmm (ITC No. 129)l lanthanide oxychlorides are inconsistent. Nuclear site symmetry analysis predicts six Raman bands. Five peaks are consistently observed, whereas the sixth remains controversial. Also, two different sets of irreducible representations are reported : 2A,, + 3Eg + Bza (or B I J + 3A2, + 3E, which include the three acoustic modes, A*,{ T,} and Em{ T,, T J . The present analysis of the polarized Raman spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
(2 reference statements)
1
6
0
Order By: Relevance
“…Thus, it is expected that related actinide(III) complexes can be prepared by applying similar techniques and methods. A number of workers have shown that this is possible and that the structural and physicochemical properties of these 4f and 5f complexes compare well. We, therefore, expect that the work described here can well be extended to the radioactive actinide elements and not only enhance the fundamental knowledge of f-element chemistry but also suggest implications for the long-term isolation and safe storage of spent nuclear fuels.…”
Section: Introductionmentioning
confidence: 69%
“…Thus, it is expected that related actinide(III) complexes can be prepared by applying similar techniques and methods. A number of workers have shown that this is possible and that the structural and physicochemical properties of these 4f and 5f complexes compare well. We, therefore, expect that the work described here can well be extended to the radioactive actinide elements and not only enhance the fundamental knowledge of f-element chemistry but also suggest implications for the long-term isolation and safe storage of spent nuclear fuels.…”
Section: Introductionmentioning
confidence: 69%
“…As for the peak shift of Raman spectra, the most of NdOCl spectrum peaks in the products obtained in our mechanochemical experiments were shifted to lower wavenumbers than those of tetragonal NdOCl crystals [19], and they were considered to be influence of the residual stress by a milling as described above sections. According to the Raman spectroscopy measurements of Cr 2 O 3 thin films [28], Y 2 O 3 -ZrO 2 barrier coatings [29], epitaxial GaN layers [30], and Al 2 O 3 single crystals [31], in the state where the stress was applied, the redshift which the peak shifted to low wavenumbers was based on the tensile stress, and the tensile stress remained in the surface of products which obtained by using a planetary ball mill.…”
Section: Structural Change Of Nd 2 O 3 and Ndoclmentioning
confidence: 93%
“…In order to confirm the possibility of chlorination from Nd 2 O 3 with CCl 4 in a tungsten carbide pot and to compare a product obtained in a zirconia pot with that in a tungsten carbide pot, the mechanochemical experiments were conducted in the same condition by a milling at 500 . The Raman shifts of tetragonal NdOCl are 118, 183, 352, and 465 cm −1 and these products were considered to be NdOCl [19]. As a reason to which measured peak positions became lower than reference values [19], since the Raman peak positions of RuO 2 shifted to lower wavenumber by residual stress [20][21][22], it was presumed that stress remained in the products even after a milling operation.…”
Section: Possibility Of Chlorination To Ndocl By Milling In Zirconia mentioning
confidence: 99%
“…The solid-state Raman spectra report five symmetrical modes that are consistent with the previously published lanthanide oxychloride literature. 28,29 In Situ Electrochemistry and Spectroscopy CV experiments conducted on LiCl-KCl with SmCl 3 solvated at low concentrations may produce an additional anodic peak in a slightly more oxidative region than that associated with the traditional SmCl 3 redox couple. A sample CV that contains this additional anodic peak, indicated with an asterisk, is reported in Figure 7.…”
Section: Synthesis and Solid-state Characterizationmentioning
confidence: 99%